Control Parametric Analysis on Improving Park Restoring Force Model and Damage Evaluation of High-Strength Structure. (11th August 2016) - Lin, Huang-bin; Tang, Shou-gao; Lan, Cheng
Abstract : In the dynamic time-history analysis of structural elastoplasticity, it is important to develop a universal mathematical model that can describe the force-displacement characteristics for restoring force. By defining three control parameters (stiffness degradation, slip closureγ, energy degradationβ ), the Park restoring force mathematical model can simulate various components. In this study, the Park restoring force has been improved by adding two control parameters (energy-based strength degradationβ e and ductility-based strength degradationβ d ). Based on the testing data, the constitutive model is input and 55 numerical models are developed to analyze the effects of various parameters on structural behavior. Conclusion . (1)β has determinative effect on structural behavior; the effect ofβ e is basically consistent with that ofβ ;α has significant effect on shear forces and bending moments;γ has significant effect on displacements and accelerations;β d has significant effect on shearing forces, acceleration, and total energy consumptions. (2) Based on the classification of four types of damage level, the recommended values forα, γ, β, β e, andβ d are presented. (3) Based on the testing data of high-strength columns, the recommended values for the five control parameters of the improved Park restoring force model are presented.